Information, expertise, and authority: the many ends of epidemics - Charters, E (Brepols, 2022)
What does it mean for an epidemic to end, and who gets to declare that it is over? This multidisciplinary spotlight issue provides eighteen case studies, each examining specific epidemics and their ends as well as the methodologies used to measure, gauge, and define an epidemic’s end. They demonstrate that an epidemic’s end is often contentious, raising issues of competing authority. Various forms of expertise jostle over who declares an end, as well as what data and information should be used to measure and define the end of an epidemic. As a result, it is more accurate to describe multiple endings to an epidemic: the medical end, the political end, and the social end. At the same time, multidisciplinary research into the ends of epidemics highlights the crucial role of information and measurement in an epidemic’s end as well as the ways in which ending forces observers to rethink and reconceptualize time. Whereas the declaration of an epidemic suggests a neatly defined period of emergency, the end is a messy process incorporating competing accounts of what went wrong and fears of the next epidemic, in which cycles of multiple diseases and overlapping social crises disrupt a simple return to normal life, articulating the nature of epidemics not just as medical phenomena, but also as fundamentally political and social. The end period therefore looks both forward and backward, often applying ‘lessons learned’ from the history of the ended epidemic to the future, in anticipation of the next outbreak. Re-envisioning the future is a way to analyse and understand the past epidemic, and thereby to restore human agency into society’s relationship with disease.